Turkish-Greek Rapprochement in the 1930s: The British Factor as a Third Party - Emine Tutku Vardağlı (Akademik İncelemeler Dergisi)
The third party effect in international relations gained popularity in 1990s in the context of conflict resolution. However, the Turkish-Greek relations in the modern era have always been discussed in reference to a third party involvement and Britain has always prevailed over the other countries as the most prominent third party. This study searches for the British influence on the Turkish-Greek rapprochement in 1930s. The British factor influence is usually taken as a matter of Great Power dominance or the “provocateur of rivalries between the two nations” from the Turkish point of view or “cooperation of allies” from the Greek point of view. Whereas, this study focuses on a specific conjuncture in which Britain acted neither as a “provocateur” nor as an “ally” for any party. In reference to the historical sources, it is documented that from the late 1920s the British approach to the Turkish-Greek affairs was altered dramatically, parallel to the overarching systemic changes in the interwar period Specifically, it is argued that the revision of British financial policy in response to the Great Depression and its retreat from the Eastern Mediterranean as a naval power directed Greece to change its foreign policy orientations with a sudden demarche and offer Turkey a peace settlement. Rather than attributing this rapprochement to the efforts of charismatic leaders, this study analyses the issue with a realist mind in reference to the British policies modified in parallel to the systemic changes during the interwar years.